Mini Research Based of Learning Material under Theme of Human Respiration System - Elisa, Dwiba; Susilaningsih, Endang; Lisdiana, Lisdiana (Journal of Primary Education)
This research aims to find out validity and reliability of mini research based learning material supplement for fifth graders primary school. This research and development (R&D) had stages started from: identifying potency and problem, collecting the data by using questionnaire, observation, interview, pre-test question and post-test, designing product in the form of mini research based learning material under theme respiration system of human as learning supplement with current developed topic about the danger of smoking for human health, validating the design done by media and material experts, revising the design based on judgment, critics, and experts? advices, and testing the products done at VB graders of Islamic Primary School Ta?allamul Huda Bumiayu. The data was analyzed descriptive qualitatively. The finding showed that the media and the subject content experts giving average score of 3.48 (87%) and 3.94 (98.33%), respectively. Based on the teacher?s judgment, the average score obtained 3.20 (80%) and judgment given by students showed average score 3.82 (95.49%). The judgment from media and subject content experts, teachers, and students showed that the supplement was reliable. The implementation of this product to measure conceptual understanding and showed improvement from 42.54 into 74.77 with N-gain 0.55, categorized as moderate. The students? attitudes dealing with smoking showed N-gain 0.39, categorized moderate with improvement score from 82.33 into 87.67, categorized to gave negative respons for smoking attitude. The learning material supplement based on mini research under theme human respiration system was valid and reliable to be used as learning materials for fifth graders.